The c-kit ligand, stem cell factor, promotes mast cell survival by suppressing apoptosis. - Iemura, A. (1994)
Stem cell factor (SCF) and its receptor (SCFR), a member of the receptor tyrosine kinase III family that is encoded by the c-kit gene, critically regulate several complex biological programs including hematopoiesis, mast cell development, cutaneous pigmentation, and gametogenesis. We show herein that mouse mast cells die rapidly after the withdrawal of SCF in vivo or in vitro, and provide morphological evidence that such mast cells undergo programmed cell death or apoptosis. We also show that when in vitro-derived mouse mast cells maintained in SCF are removed from SCF-containing medium for only 5 or 6 hours, the cells' genomic DNA exhibits the ladder-like pattern of oligonucleosome-sized fragments typical of apoptosis. These findings demonstrate that SCF can regulate the survival of a cellular lineage which expresses the SCFR by suppressing apoptosis. They also identify a mechanism that can result in striking and rapid reductions in the size of tissue mast cell populations without histological evidence of the concomitant induction of a significant inflammatory response.